Measuring economc growth and the new economy - Patrick Vanhoudt; Luca Onorante (EIB Papers, 2001)
For years the economics profession has been puzzled by one of the most perplexing economic problems - the overall slowdown in the growth rate of labour productivity since 1973. Not only was the deceleration a worldwide trend, the growth of productivity also turned out to be markedly slower in the US than in any other industrialized nation. In spite of many hypotheses, the phenomenon has remained, however, much of an academic mystery, often labelled with the analogy 'death from a thousand cuts'. Yet today a reverse situation seems to have occurred. The contemporary brainteaser is indeed no longer why the US has been suffering from the slowest expansion of output per worker among the highly developed economies. Now the question is rather how the rapid increases in US labour productivity in the 1990s can be explained, and why other nations do not perform equally well.
Keywords: 330; Arbeitsproduktivität; Messung; Informationstechnik; USA; New Economy